The Impact of JENG IVA CANTIKS Program on IVA Inspection Coverage at Kamal Primary Health Center - Khadijah, Khadijah; Susanti, Eny; M. Suhron; Jannah, Rohilatul (Universitas Muhammadiyah Sidoarjo, 2026)
In 2022, the incidence and mortality rates of cervical cancer were high in Indonesia, but coverage of National cervical cancer screening still only 12% done. This study aimed to examine the effect of the JENG IVA CANTIKS program on improving IVA screening coverage. A quasi-experimental design was employed. The dependent variable was IVA screening coverage, and the independent variable was the JENG IVA CANTIKS program. The study population consisted of all villages within the health center’s catchment area, totaling 10 villages, with the sample selected through total sampling of all 10 villages. Data were analyzed using a Wilcoxon Signed Ranks Test. The results indicated a significance value of 0.005 (< 0.05) in the Wilcoxon Signed Ranks Test, demonstrating that the JENG IVA CANTIKS intervention had a significant effect on IVA screening coverage.